High-frequency electrochemical double layer capacitor based on carbon nanotubes ink coated eggshell membrane electrodes. (January 2022) - Das, S.; Manuraj, M.; Rakhi, R.B.; Ajayaghosh, A.
Highlights: Fabrication of a high-frequency symmetric EDLC with CNT ink coated ESM electrodes and a bare ESM separator. At a frequency of 120 Hz, the device exhibits a phase angle of −75°. The device retains the nearly rectangular shape of the cyclic voltammogram even at a scan rate of 1 kV s −1 . The fabricated EDLC exhibits an excellent cycling stability of 98.6% after 200, 000 cycles. ABSTRACT: A high-frequency symmetric electrochemical double layer capacitor (EDLC) is fabricated using carbon nanotubes (CNT) ink coated eggshell membrane (ESM) electrodes and a bare ESM separator soaked in 1 M KOH electrolyte. Hydrolysed ESM acts as a suitable surfactant for the uniform dispersion of CNTs in water forming the CNT ink. The ESM electrodes are prepared by the simple dipping and drying process of ESM substrates in CNT ink suspension. At a constant current density of 10 mA cm −2, the fabricated EDLC cell exhibits an areal capacitance of 4 mF cm −2 . At a frequency of 120 Hz, it shows a phase angle of -75° The constructed CESM based capacitor demonstrates a frequency response as fast as 4500 Hz at a phase angle of -45° The high-frequency capacitor retains the nearly rectangular shape of the cyclic voltammogram even at a scan rate of 1 kV s   −   1 and excellent cycling stability of 98.6% after 200, 000 cycles. The results demonstrate that the EDLC based on ESM and CNTs has excellent potential for biomaterial based high-frequency electronic device applications. Graphical abstract: Image, graphical abstract